Evaluasi Penggunaan Obat dan Identifikasi Drug Related Problems (DRPs) Pada Pasien Rawat Inap Diabetes Melitus tipe 2 di Rumah Sakit Umum Royal Prima Marelan - Novelin Lubis, Natasya Twenty; Yunus, Muhammad; Br. Ginting, Astriani Natalia (Jurnal Kesehatan Nusantara (JKN), 2025)
Type 2 diabetes mellitus (type 2 DM) is a chronic metabolic disease that requires long-term pharmacotherapy. Inappropriate medication use can lead to Drug-Related Problems (DRPs), which can affect the success of therapy. This study used a retrospective descriptive method with a cross-sectional approach. Data were obtained from the medical records of 50 patients with type 2 DM who were hospitalized between July and September 2024. DRPs were identified based on the American Society of Hospital Pharmacists (ASHP) classification. The results showed that most patients were female (56%) with a dominant age of 50–59 years. The most frequently prescribed antidiabetic drug was metformin (40.7%), followed by insulin (33.72%), and glimepiride (13.95%). The most common types of DRPs were drug interactions (95.65%), and one case of inappropriate drug selection (4.35%). The conclusion of the study is that the use of drugs in type 2 DM patients in this hospital is generally in accordance with the guidelines, however there is still the potential for DRPs, especially in the form of drug interactions.